Optimalisasi Peran Hukum Perusahaan Pelayaran Terhadap Pencegahan Pencemaran Laut Oleh Sampah Sesuai Marine Pollution (Marpol) 73/78 Annex-V Dari Kapal - Christine Astrid Aurora; Dhaniswara K. Harjono; Binoto Nadapdap (Syntax Corporation Indonesia, 2023)
Plastic waste has a serious impact on the marine environment, threatening more than 800 marine species, and can affect the food chain down to humans. The aim of this research is firstly to find out, analyze and explain issues related to strategies for preventing marine pollution from ship waste. This research is normative legal research which considers research as analysis. The data analysis technique used is through data collected from legal materials with descriptions in effective, orderly and logical sentences so as to simplify the analysis of the results of the problem formulation. Results of the research Currently, MARPOL Regulation 73/78 Annex V is an important international legal instrument to prevent marine pollution by waste from ships. This regulation prohibits the dumping of waste into the sea, except under certain conditions. In the implementation and management of waste on board ships, activities ranging from waste collection to disposal, must all be carried out in accordance with the procedures regulated in Annex V MARPOL 73/78, if If waste management is not carried out according to predetermined procedures, waste dumping will occur anywhere and wherever the ship is located so that in the future waste that is thrown carelessly can cause pollution in the sea.